2021
DOI: 10.1016/j.jaim.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of Andrographis paniculata extract in healthy adults – An open-label study

Abstract: Background Andrographis paniculata (Burm.f.) Nees has been well-researched for its immunomodulatory effects. Objective(s) To investigate the immunomodulatory effects of standardized A. paniculata extract (SAPE) in healthy adults. Materials and methods The study was an open-label, single-centre study conducted for 30 days. Thirty participants with absolute lymphocyte counts of 1000–4000 cells/mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
1
17
0
3
Order By: Relevance
“…In fact, AP water extract is a widely used herbal medicine and has a long history of use in Asian countries; the safety clinical profiles have been established in patients with different diseases (Hossain et al, 2021; Worakunphanich et al, 2021). A recent report also demonstrated that supplementation of standardized AP extract in healthy subjects was found to be safe and tolerable (Rajanna et al, 2021). Hence, the current Phase II clinical trial further confirms the safety of AP in esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, AP water extract is a widely used herbal medicine and has a long history of use in Asian countries; the safety clinical profiles have been established in patients with different diseases (Hossain et al, 2021; Worakunphanich et al, 2021). A recent report also demonstrated that supplementation of standardized AP extract in healthy subjects was found to be safe and tolerable (Rajanna et al, 2021). Hence, the current Phase II clinical trial further confirms the safety of AP in esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 94%
“…IFN-γ is secreted by Th1 cells and enhances cellular immune function. Therefore, the levels of IL-4, IL-12, and IFN-γ cytokines can reflect the status of humoral and cellular immunity [ 35 ]. Our results showed that the levels of IL-4, IL-12, and IFN-γ in the CYC group were significantly decreased, indicating that CYC inhibited the cellular and humoral immunity of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al demonstrated that andrographolide treatment reduces hepatic neutrophil/macrophage infiltration, local inflammation, and liver damage in thioacetamide-induced mouse hepatic fibrosis . Rajanna et al has shown that standardized A. paniculata extract (SAPE) increased T cells and T helper cells and significantly increased IFN-γ, IL-4, and decreased IL-2 at day 30 in healthy adults . It has also been reported that andrographolide can suppress humoral and cellular adaptive immune responses.…”
Section: Mechanistic Basis Of Action Of the Phytochemicals Used For T...mentioning
confidence: 99%
“…105 Rajanna et al has shown that standardized A. paniculata extract (SAPE) increased T cells and T helper cells and significantly increased IFN-γ, IL-4, and decreased IL-2 at day 30 in healthy adults. 106 It has also been reported that andrographolide can suppress humoral and cellular adaptive immune responses. In vitro, this molecule inhibited T cell proliferation and cytokine release in response to allogenic stimulation.…”
Section: ■ Mechanistic Basis Of Action Of the Phytochemicals Used For...mentioning
confidence: 99%